Frequency and Clinical Profile of Vitamin D Deficiency Rickets in Children: A Retrospective Study - Minhas, Amna; Iqbal, Zahra; Tariq, Muhammad Habibullah; Sabir, Muhammad Ali; Qammar, Bilal; Afgan, Sher (Journal of Rawalpindi Medical College, 2026)
Objective: This study aimed to determine the frequency and clinical profile of vitamin D deficiency rickets in children. Methods: This retrospective descriptive study was conducted at King Edward Medical University from March 2024 to June 2025. A total of 265 children aged 6 months to 12 years, diagnosed with vitamin D deficiency rickets based on clinical, biochemical, and radiological findings. Data regarding demographics, socioeconomic status, feeding practices, sunlight exposure, clinical presentation, laboratory parameters, and radiological features were retrieved from medical records. Results: The mean age of affected children was 3.8 ± 2.1 years, with most cases occurring under 5 years of age (75.1%). Males (58.1%) were more frequently affected than females (41.9%). Low socioeconomic background (63%), exclusive breastfeeding without supplementation (55.1%), and inadequate sunlight exposure (69.1%) were significant risk factors. The most common clinical features were bowing of legs (58.9%), widened wrists (54.3%), growth retardation (50.6%), and delayed motor milestones (42.3%). Hypocalcemic seizures occurred in 10.9% of patients, predominantly among infants. Biochemical findings showed hypocalcemia (7.9 ± 1.1 mg/dL), low phosphorus (3.4 ± 0.9 mg/dL), elevated alkaline phosphatase (1082 ± 354 IU/L), and markedly low vitamin D (11.7 ± 4.2 ng/mL). Conclusion: Vitamin D deficiency rickets remains a prevalent pediatric health issue with significant clinical and developmental consequences. The findings of this study highlight the critical role of nutritional insufficiency, inadequate sunlight exposure, and socioeconomic disparities in perpetuating the disease. Keywords: Vitamin D Deficiency, Rickets, Epidemiology, Malnutrition.